The Benthic Megafaunal Assemblages of the CCZ (Eastern Pacific) and an Approach to their Management in the Face of Threatened Anthropogenic Impacts - Tilot, Virginie; Ormond, Rupert; Moreno Navas, Juan; Catalá, Teresa S. (Frontiers in Marine Science, 2018)
We present here the results of a comprehensive UNESCO/IOC baseline study of the megafaunal assemblages of the metallic nodule ecosystem of 5 areas within the Clarion Clipperton Fracture Zone (CCFZ) of the eastern Pacific Ocean. The work was undertaken with a view to interpreting the structure of the epifaunal populations associated with the benthic biotopes being targeted for mining and developing an appropriate set of management tools and options. The general characteristics of the nodule ecosystem and its sensitivity to deep-sea mining are discussed in relation to water masses, ocean circulation from the surface to the seabed, the nepheloid layer and processes taking place at the sediment interface. Management tools considered include species diversity, vulnerability indexes, GIS systems, zoning, and 3D rapid environmental assessment (REA). These monitoring strategies are developed for application on one of the UNESCO/IOC baseline study sites.